P131 Understanding Health Beliefs And Behaviour In Workers With Occupational Asthma. (10th November 2014) - Walters, GI; Robertson, AS; Burge, PS; Ayres, JG; Soundy, AS
Abstract : Introduction: Long delays from symptom onset to the diagnosis of occupational asthma have been reported in the UK, Europe and Canada and workers are often reluctant to seek medical help or workplace solutions for their symptoms. 1, 2 Reducing this delay could improve workers' quality of life, and reduce the societal cost of occupational asthma. This study aimed to explore reasons behind such delays. Methods: A purposive sample of 20 individuals diagnosed with, or under investigation for, occupational asthma (median age=52; 70% male; 80% white British) undertook a single semi-structured interview. Interviews were transcribed verbatim and thematic analysis was undertaken in order to explore health beliefs and identify barriers to diagnosis. Results: Four themes were identified: (1) workers' understanding of symptoms, (2) working relationships, (3) workers' course of action and (4) workers' negotiation with healthcare professionals. Understanding of symptoms varied between individuals, from a lack of insight into the onset, pattern and nature of symptoms, through to misunderstanding of what they represented, or ignorance of the existence of asthma as a disease entity. Workers described reluctance to discuss health issues with managers and peers, through fear of job loss and a perceived lack of ability to find a solution. Conclusion: The evolution of workers' understanding depended upon how actively they looked to define symptoms or seek a solution. Proactive workers were motivated to seek authoritative help and negotiate inadequate healthcare encounters with GPs. In summary there appear to be a number of key influences motivating a worker to seek an explanation for their symptoms or a definitive solution, which are represented in the model in Figure 1 . Understanding workers' health beliefs will enable policy makers and clinicians to develop better workplace interventions for identifying occupational asthma. References: Fishwick D et al . Prim Care Respir J 2007;16: 304–10 Poonai N et al . Can J Public Health 2005;96:230–3